2019
DOI: 10.1002/bit.27191
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling and resolving inefficient glucolipid biosurfactants production through quantitative multiomics analyses of Starmerella bombicola strains

Abstract: Glucolipids (GLs) are glycolipid biosurfactants with promising properties. These GLs are composed of glucose attached to a hydroxy fatty acid through a ω and/or ω‐1 glycosidic linkage. Up until today these interesting molecules could only be produced using an engineered Starmerella bombicola strain (∆ugtB1::URA3 G9) producing GLs instead of sophorolipids, albeit with a very low average productivity (0.01 g·L−1·h−1). In this study, we investigated the reason(s) for this via reverse‐transcription quantitative po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…SLs has been regarded as a green and sustainable biosurfactants, but their high production costs limit largescale application and development. [21][22][23] Coupling fermentation on the basis of in-situ product separation is one of the most effective ways to reduce production costs and improve productivity (Table 2). Wang designed a simple in-situ separation device coupled with the bioreactor and adopted high cell density fermentation to achieve high-efficient production of SLs.…”
Section: Discussionmentioning
confidence: 99%
“…SLs has been regarded as a green and sustainable biosurfactants, but their high production costs limit largescale application and development. [21][22][23] Coupling fermentation on the basis of in-situ product separation is one of the most effective ways to reduce production costs and improve productivity (Table 2). Wang designed a simple in-situ separation device coupled with the bioreactor and adopted high cell density fermentation to achieve high-efficient production of SLs.…”
Section: Discussionmentioning
confidence: 99%
“…During process development, we recommend to generate highly pure standards of the biosurfactant mixture and then use these ‘standards’ (consisting of a mixture of congeners) to analyse broth samples containing the same mixture of biosurfactant congeners in the same ratio’s (Roelants et al ., 2016; Lodens et al ., 2020). Important to note is that one should carefully consider the ratio’s of the compounds/peaks in the samples versus the standards.…”
Section: Process Development Towards the Scale‐up And Commercial Applmentioning
confidence: 99%
“…If these ratio’s remain the same this method is valid. Because the latter is not always the case, it is also recommended – if possible – to generate highly pure standards of the most abundant congeners available in the mixture, so these can be quantified (absolutely) separately, for example non‐acetylated C18:1 acidic sophorolipids, di‐acetylated C18:1 lactonic sophorolipids, non‐acetylated C18:1 acidic glucolipids (Roelants et al ., 2016; Lodens et al ., 2020). This will thus be a case to case issue, but the authors of this work active on these aspects, typically make sure both options are at hand.…”
Section: Process Development Towards the Scale‐up And Commercial Applmentioning
confidence: 99%
“…104,105,106 S. bombicola has a non-pathogenic nature and the capacity to produce large quantities of biosurfactant with a sophorolipid structure (around 177 g/L) from agricultural waste products and under conditions of a high concentration of hydrophobic compounds, making it promising for industrial applications as an emulsifying agent and stabilizer, especially in the food industry. 107,108,109 Yeasts of the genus Saccharomyces are also widely explored in the food area. Studies conducted as far back as the 1980s reported the use of intracellular compounds with emulsifying activity derived from yeasts of the genera Saccharomyces, such as S. cerevisiae, demonstrating the possibility of extracting mannoproteins in an easy manner from the cell wall that exhibit stability at different temperatures.…”
Section: Biosurfactant-producing Yeastsmentioning
confidence: 99%
“…This yeast is considered to be a teleomorph of C. bombicola due to the high identity of the genetic material between the two (more than 98%) and its sexual reproduction stage 104,105,106 . S. bombicola has a non‐pathogenic nature and the capacity to produce large quantities of biosurfactant with a sophorolipid structure (around 177 g/L) from agricultural waste products and under conditions of a high concentration of hydrophobic compounds, making it promising for industrial applications as an emulsifying agent and stabilizer, especially in the food industry 107,108,109 …”
Section: Biosurfactantsmentioning
confidence: 99%